2022
DOI: 10.1155/2022/7011789
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Evaluation of the Antiasthmatic Activity of Carissa opaca in Animal Models

Abstract: Carissa opaca Stapf ex Haines (C. opaca) fruit is used traditionally in the treatment of respiratory illnesses including asthma. However, there is no scientific evidence supporting its antiasthmatic activity. The current study was conducted to evaluate its antiasthmatic effects using in vivo and in vitro approaches. The methanolic crude extract of C. opaca fruit (Co.Cr.) was used and in vivo antiasthmatic activity was carried out using ovalbumin- (OVA-) sensitized and OVA-challenged BALB/c mice. In in vitro br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%